Pyometra in the bitch - VERVERIDIS (Χ. ΒΕΡΒΕΡΙΔΗΣ) H.; BOSCOS (Κ. ΜΠΟΣΚΟΣ) C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Pyometra is the final stage of a developing cystic endometrial hyperplasia. The aetiopathogenesis remains unresolved. Repeated barren oestrus cycles, excessive use of progestins or oestrogens as well as a bacterial infection of the endometrium contribute to the development of pyometra. Pyometra sould be suspected if, a post-estrous, usually aged bitch is presented with a varying degree of depression, inappétence, polydipsia, polyuria, dehydration, abdominal distension, manifesting or not an abnormal vulvar discharge. Abdominal radiography or ultrasonograpy can confirm the diagnosis. Laboratory findings prove to be helpful in diagnosis, prognosis and treatment. Ovariohysterectomy is the treatment of choice along with proper fluid and antimicrobial therapy for aged or severely ill bitches or for those with low breeding value. Medical treatment with Prostaglandin F2a combined with bactericidal antibiotics can be recommended, provided that the bitch is young, of high breeding value and with mild clinical signs.